-7/4+5/6-4/3
You asked:
Evaluate the expression: \(\frac{-7}{4} + \frac{5}{6} - \frac{4}{3}\)
MathBot Answer:
\[ \frac{-7}{4} + \frac{5}{6} - \frac{4}{3} = - \frac{9}{4} = -2.25 \]
The sum can be computed by rewriting each term over a common denominator, where the least common denominator of \(\frac{-7}{4}\), \(\frac{5}{6}\), and \(\frac{-4}{3}\) is \(12\). \[ \begin{aligned} \frac{-7}{4} + \frac{5}{6} - \frac{4}{3} &= \frac{-7 \cdot 3}{4 \cdot 3} + \frac{5 \cdot 2}{6 \cdot 2} + \frac{-4 \cdot 4}{3 \cdot 4} \\ &= \frac{-21 + 10 + -16}{12} \\ &= \frac{-27}{12} \\&= - \frac{9}{4} \end{aligned} \]